A Study of Cutaneous Adverse Drug Reactions and their Association with Autoimmune Diseases at a Tertiary Centre in South-West Rajasthan, India - Shweta Rana; Kalpana Gupta; Nidheesh Agarwal; Ahamed Noor Mqnsoon Ahamed (Wolters Kluwer Medknow Publications, 2021)
Background: Cutaneous adverse drug reactions (CADRs) comprise about 30% of all adverse drug reactions and observed in 2-3% of hospitalized patients by wide variety of offending agents. Aims: To study the clinical patterns, causative drugs and their association with autoimmune diseases in CADR patients. Materials and Methods: A total of 174 CADR patients who presented to the dermatology OPD over a period of 18 months (1 July 2015 to 31 Dec 2016) were considered for the study. Detailed history, clinical examination, hematological, and biochemical investigations were recorded. The venereal disease research laboratory test, HIV (ELISA), and histopathological examination were done wherever indicated. Results: The mean age of the patients with cutaneous drug eruptions was 40.2 years. Most of them (31.0%) were in the age group of 41-50 years. There were 93 (53.4%) males and 81 (46.5%) females with the M:F ratio of 1.5:1. The most common eruption observed was maculopapular rash in 33.3% followed by fixed drug eruption (17.2%) and lichenoid dermatitis' (11.5%). The drugs most commonly responsible for CADRs were antimicrobials (n = 68, 39%) with fixed dose combination of fluoroquinolones with nitroimidazoles (n = 42). We also noticed that a total of 42 patients out of 174 had comorbities in the form of diabetes (n = 27, 15.5%), hypothyroidism (n = 9, 5.1%), rheumatoid arthritis (n = 3, 1.7%), vitiligo (n = 2, 1.1%), and SLE (n = 1, 0.5%). Conclusion: Cutaneous ADR patterns and the drugs causing various reactions are changing every year, which may be because of the introduction of newer molecules and changing trends in the use of drugs. In our study, a significant relation of CADRs with autoimmune diseases (P value = 0.004) was also observed.